2007
DOI: 10.1002/cncr.22847
|View full text |Cite
|
Sign up to set email alerts
|

Low locoregional failure rates in selected breast cancer patients with tumor‐positive sentinel lymph nodes who do not undergo completion axillary dissection

Abstract: The synthesis and optimization of novel bioactive components is key to the development of antifouling marine coatings. It was recently demonstrated that medetomidine (MM) has perfect antibarnacle behavior along with good ecological properties. To investigate the applicability of MM in self‐polishing marine paints, a large set of mixtures of MM with two commercial alkyd resins (ARs) was prepared. The nature and strength of the intermolecular interaction as a function of composition in both the liquid and solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 77 publications
(65 reference statements)
3
90
0
5
Order By: Relevance
“…Invasive lobular 4 (13) 21 (13) 13 (20) 6 (15) 5 (25) Select studies of patients with positive SLN and who did not undergo ALND have demonstrated low regional recurrence rates in the setting of adjuvant systemic therapy and RT (Table 5). 1,[5][6][7][8][9][10][11][12][13][14]28 Those series differed with respect to the length of median follow-up, the definition of a positive SLN, reasons for omitting ALND, and the receipt of systemic therapy. Although several of those reports 1,5,7,11 described the RT fields used, none reported treatment outcomes stratified by RT field design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Invasive lobular 4 (13) 21 (13) 13 (20) 6 (15) 5 (25) Select studies of patients with positive SLN and who did not undergo ALND have demonstrated low regional recurrence rates in the setting of adjuvant systemic therapy and RT (Table 5). 1,[5][6][7][8][9][10][11][12][13][14]28 Those series differed with respect to the length of median follow-up, the definition of a positive SLN, reasons for omitting ALND, and the receipt of systemic therapy. Although several of those reports 1,5,7,11 described the RT fields used, none reported treatment outcomes stratified by RT field design.…”
Section: Discussionmentioning
confidence: 99%
“…1 Hwang et al reported results from 196 patients who were treated at The University of Texas M. D. Anderson Cancer Center. 6 In that study, among 89 patients who received RT, 56 received axillary-specific RT. At a median follow-up of 30 months, only 1 patient had a regional recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account data on axillary recurrence after negative SLN, we can expect clinical manifestations in only 3-6 (0.3-0.6%) of those patients. Furthermore, six series (n = 583) of selected SLN-positive patients who did not undergo cALND reported similar axillary recurrence (0.5% at a median follow up of 31 months) [32][33][34][35][36][37]. These rates seem acceptably low and it is very unlikely that they would ever reach 10%, the level at which local recurrence have a detectable impact on survival according to the latest Early Breast Cancer Trialists Collaborative Group overview [38].…”
Section: Discussionmentioning
confidence: 99%
“…(20)(21)(22)(23)(24) The biggest concern with utilizing SLNB is its false-negative rate, which is about 2-10% as reported in most studies. In this study, we compared the disease-free survival of pN0 patients and we found that the prognosis of the pN0 patients who were treated with SLNB only was significantly better than that of the patients who were treated with ALND without SLNB.…”
Section: Discussionmentioning
confidence: 99%